Currículo integrado : percepção da interdisciplinaridade na formação de enfermeiros - Santos, Nadja Romeiro dos (2014)
In Brazil, the discussions about the interdisciplinary began in the 70s, in order to investigate the intensity of exchanges between experts and the degree of integration of the disciplines in a research project. This study discuss about the issues in the nursing training within the proposed integrated and interdisciplinary curriculum, aiming to check the students' perceptions about interdisciplinary in the undergraduate nursing degree from a public institution of higher education. It is a quantitative, a qualitative and an exploratory research, that as a data collection instrument, were used a structured questionnaire, with both open-ended and closed-ended questions. The questions were constructed from the previous reading of the Political-Pedagogical Project(PPP) of the Nursing undergraduate program, that was distributed around the five chapters of PPP, regarding the objective of the course, the profile of egress, the general skills and competencies needed, the specific abilities and competencies, and the curricular organization. This questionnaire was administered to 51 students of fourth and fifth year of that course the data was collected between June and July 2013,the Qualitative data were analysed by the content analysis. For the quantitative analysis, we built a Likert attitudinal instrument. The results of this research contributed to the development of a product, which is an intervention project, which will provide improved training in nursing, support base for changes in current practices, with emphasis on the integration of education, service and community for the strengthening of the integrated and interdisciplinary curriculum. It is concluded that the students understand the interdisciplinary movement as strengthening the relationship with the reality, recognizing the need for integration and dialogue of the actors involved in the teaching-learning process, identifying, however, weaknesses in the construction process of this practice in relation to the development of interdisciplinary since the beginning of the course.